Case Report: Idiopathic Sigmoid Volvulus in an 11-Year-Old Boy – A Rare Pediatric Surgical Emergency - ramesh, Ajay; chordia, Dhaksay; Raj, Jai Durai (Journal of Neonatal Surgery, 2025)
Background: Sigmoid volvulus, defined as the torsion of the sigmoid colon around its mesentery, is a rare cause of intestinal obstruction in children, accounting for less than 0.01% of pediatric cases in India. It is typically associated with anatomical or functional abnormalities; however, idiopathic presentations are exceedingly uncommon. Case Presentation: We report the case of an 11-year-old previously healthy male who presented with a two-day history of abdominal pain and vomiting. Clinical and radiological evaluation revealed features consistent with sigmoid volvulus, including the classical “coffee bean” sign on abdominal radiography and a 180° torsion on CT imaging. Following initial stabilization, the patient underwent emergency laparotomy. Intraoperative findings confirmed a viable but twisted sigmoid colon, which was detorsed, resected, and primarily anastomosed. The postoperative course was uneventful, and histopathology ruled out any underlying congenital anomalies. Conclusion: This case highlights the need to consider sigmoid volvulus in the differential diagnosis of acute abdomen in children, even in the absence of predisposing factors. Early diagnosis through imaging and timely surgical intervention are critical to preventing complications and ensuring positive outcomes.